Peran Media Elektronik Berbasis Video Pembelajaran Melalui Aplikasi Kinemaster. Studi Kasus pada Siswa Kota Makassar - Badruddin Kaddas; Anrayani Anrayani (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: The Role of Video-Based Electronic Media Learning Through Kinemaster Applications. Case Study in Makassar City Students. This study aims to describe (1) the role of learning video-based electronic media through the Kinemaster application, (2) inhibiting and supporting factors for learning video-based media through the Kinemaster application in the midst of a pandemic and, (3) the application of learning video-based electronic media through the Kinemaster application in terms of planning, implementation, and evaluation related to the role of video-based electronic media learning through the Kinemaster application of students in the city of Makassar. The results showed that the role of video-based electronic media learning through the Kinemaster application in the midst of a pandemic can be said to play a very important role, because with the existence of electronic media, humans can provide communication between each other both between individuals and individuals with a group of humans. Likewise with learning videos that play an important role in the field of education during the Covid-19 pandemic, because learning videos made by teachers through the Kinemaster application are one of the media that is very suitable for teachers to use as an intermediary for the teaching and learning process delivered to students during the implementation of online learning during the pandemic.